Application of Strict Liability Principles Against Illegal Karst Rock Mining Leading to Environmental Damage - Widowaty Yeni (EDP Sciences, 2021)
Illegal mining of karst rocks in Gunungkidul Regency is increasingly rampant, resulting in environmental damage and casualties. The proposed problem is how can the principle of strict liability be applied to illegal karst mining actors? What is the concept that should be done in the future to abolish illegal karst rock mining to prevent further environmental damage? The research was a socio-legal study with primary and secondary data. The research was conducted in Gunungkidul, Indonesia by taking samples in the village of Ponjong. The results of the study showed that the perpetrators of illegal karst rock mining so far have never been imposed to the principle of strict liability. Ironically, there have been no objections from the public so far against mining companies. The community around the mining area is employed by the company, while the needs of the community are met. Hence, no protest occurred even though the mining caused environmental damage. The concept that should be carried out in the future to prevent further illegal mining is the improvement of law enforcement. Although action has been taken against illegal miners with revocation of permits, a reformulation of regulations by imposing criminal sanctions on perpetrators is necessary to become a deterrent.